How much graphene in space?. Issue 3 (3rd October 2019) - Li, Qi; Li, Aigen; Jiang, B W
ABSTRACT: The possible presence of graphene in the interstellar medium (ISM) is examined by comparing the interstellar extinction curve with the ultraviolet absorption of graphene calculated from its dielectric functions experimentally obtained with the electron energy loss spectroscopy (EELS) method. Based on the absence in the interstellar extinction curve of the $\sim \! 2755\, {\rm \mathring{\rm A} }$ π–π* electronic interband transition of graphene, we place an upper limit of $\sim \! 20\, {\rm ppm}$ of C/H on the interstellar graphene abundance, exceeding the previous estimate by a factor of $\sim \, $ 3 which made use of the dielectric functions measured with the spectroscopic ellipsometry (SE) method. Compared with the SE method which measures graphene in air (and hence its surface is contaminated) in a limited energy range of $\sim \, $ 0.7–5 $\, {\rm eV}$, the EELS probes a much wider energy range of $\sim \, $ 0–50 $\, {\rm eV}$ and is free of contamination. The fact that the EELS dielectric functions are substantially smaller than that of SE naturally explains why a higher upper limit on the graphene abundance is derived with EELS. Inspired by the possible detection of C24, a planar graphene sheet, in several Galactic and extragalactic planetary nebulae, we also examine the possible presence of C24 in the diffuse ISM by comparing the model IR emission of C24 with the observed IR emission of the Galactic cirrus and the diffuse ISM towards l = 44°20′ and b = −0°20′. An upper limit of $\sim \!20\, {\rm ppm}$ on C24 is also derived from the absence of the characteristic vibrational bands of C24 at $\sim \, $ 6.6, 9.8, and 20 $\, {\rm μ m}$ in the observed IR emission.